Public Relations and New Media in Employee Relations for Enhancing Employee’s Loyalty During the Pandemic - Trifosa Joan Ervani; Lina Sinatra Wijaya (Universitas Pendidikan Ganesha, 2021)
The Covid 19 pandemic occurred nowadays has resulted in many employees resigning due to discomfort at work. Therefore, every company needs to carry out an employee relations program to increase employee’s loyalty, especially during this pandemic. The aim of this study is to determine the employee’s loyalty which was formed by the implementation of the employee relations program carried out by Public Relations using new media during the pandemic. Data collection is done by conducting observations, documentation, and interviews. The results of this study shows that there are five forms of employee relations programs done to increase employee’s loyalty, among others, education and training programs, outstanding work motivation programs, award programs, special event programs, and internal communication media programs. The success of those employee relations program are shown by a decrease in the percentage of employee resignation, from 40% to 20% in one year. Evidence of employee’s loyalty formed by the employee relations program can also be seen from several attitudes and actions of employees that include obedience and compliance, responsibility, willingness to cooperate, sense of belonging, interpersonal relationships, and fondness for work. In addition, personal touch to employees has the greatest impact to increase employee’s loyalty to the Company.